The grand plan to fix everything - Krishnaswami, Uma, 1956- (Atheneum Books for Young Readers, 2011)
Eleven-year-old Dini loves movies, and so when she learns that her family is moving to India for two years, her devastation over leaving her best friend in Maryland is tempered by the possibility of meeting her favorite actress, Dolly Singh.